Design and Implementation of PID Control-based FSM Algorithm on Line Following Robot - Al Tahtawi, Adnan Rafi; Somantri, Yoyo; Haritman, Erik (Politeknik Sukabumi, 2016)
Finite State Machine (FSM) is a control system methodology that describes systemâs behavior using three things, namely: state, event, and action. On a program, the system would be in one active state. The system can switch or move to another state if it gets a certain input or event.Â In this paper, FSM based on Proportional-Integral-Derivative (PID) controller algorithm will be implemented on line follower robot. PID controller is one of system control methods that many used recently. FSM based on PID controller is implemented to keep robot tracking the line trajectory as well. The test result shows that designed algorithm can work well and can be used as a based algorithm of this robot.